A Study on the Characteristics of Spatial and Temporal Evolution of Ozone Pollution in Chengdu (2014 - 2016). (May 2019) - Liu, Hefan; Song, Danlin; Huang, Fengxia; Lu, Chengwei; Zhang, Xin
Abstract: This study conducted an in-depth research on the characteristics of spatial and temporal evolution of ozone pollution by analyzing the 2014-2016 observation data from the state-controlled monitoring sites of ambient air quality in Chengdu. The result shows 1) that the 90th Percentile Daily Maximum 8-Hour Average O3 Concentrations of Chengdu in 2014, 2015 and 2016 are 147μg/m 3, 183μg/m 3 and 167μg/m 3, respectively; 2) that the trends of concentration change of O3 at the seven state-controlled monitoring sites for assessment of the air quality of Chengdu are exactly matched, i.e. unimodal distribution, high during the daytime and low at night with hourly minimum concentration of O3 that is 5 8 μg/m 3 ; 3) that there is a rather obvious negative correlation between NO2 and O3 and that the correlation coefficient ranges from -0.931 to -0.565; and 4) that the ozone pollution in the west of Chengdu is more serious than that in the east of Chengdu in general and that the more serious the pollution is, the bigger the area with high concentration of O3 is.